2019
DOI: 10.1186/s12884-019-2632-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep duration during pregnancy on the risk of gestational diabetes in the Japan environmental and Children’s study (JECS)

Abstract: BackgroundGestational diabetes mellitus (GDM) has serious effects on both mother and child. Like Type 2 Diabetes Mellitus, it is increasing in prevalence world-wide. In addition to obesity, sleep duration has been named an important risk factor. Using a large cohort study, including data from 48,787 participants of the Japan Environment and Children’s Study (JECS), we examined the association between sleep duration and both random blood glucose levels and GDM rates during pregnancy.MethodsRandom blood glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In Japanese medical practice, glucose-tolerance screening and testing for GDM is performed as a universal screening for every woman according to the protocols of the Obstetrics Society or Diabetes Society of Japan, depending on the local institution, using a two-step protocol [ 26 , 27 ]. All pregnant women participating in JECS underwent the screening procedure for GDM diagnosis during both early and late pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…In Japanese medical practice, glucose-tolerance screening and testing for GDM is performed as a universal screening for every woman according to the protocols of the Obstetrics Society or Diabetes Society of Japan, depending on the local institution, using a two-step protocol [ 26 , 27 ]. All pregnant women participating in JECS underwent the screening procedure for GDM diagnosis during both early and late pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have determined that prolonged exposure to environmental psychological stress is related to maternal hyperglycemia during pregnancy, which may increase the risk of GDM [ 63 ]. Similarly, the use of antidepressant and psychotropic medications, smoking, and poor sleep hygiene have also been shown to be risk factors for GDM [ 64 , 65 , 66 ].…”
Section: Risk Factors For Gdmmentioning
confidence: 99%
“…Pregnant mothers possibly gain nearly thirty percent of the mass in fatty tissues and overweight are few probable variables for diabetes in pregnancy (De Souza et al, 2015). The consumption of antidepressants and psychotropic drugs, smoking (Hosler et al, 2011), and improper sleep (Myoga et al, 2019) Moses et al, 1997). Recent studies suggested the importance of environmental exposure like toxic metals (Varshavsky et al, 2019), air pollution (Elshahidi 2019), and chemicals (Ehrlich et al, 2016) in the development of GDM.…”
Section: Factors That Cause Gdmmentioning
confidence: 99%